2022
DOI: 10.5530/pj.2022.14.23
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Compound from Endophytic Pseudomonas azotoformans UICC B-91 of Neesia altissima (Malvaceae)

Abstract: Antimicrobial activity analysis were regarding to disc diffusion. 10,11 The antimicrobial activity was measured by diameter of clear zone minus diameter of disc diffusion. Thin Layer Chromatography (TLC)TLC analytical, TLC-bioautography and semipreparative separation were performed on aluminium silica TLC F254 plates. The TLC plates were developed with mobile phase chloroform: methanol (9:1) (F1, F3, F4, and F5) and hexane: ethyl acetate (7:3) (F2). Screening for antimicrobial compound conducted by TLC-bioauto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…KB has united a variety of interactions, such as those between genes and proteins, elements and reactions, medications and illnesses, and organisms and cells (Kanehisa et al 2019 ). Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ).…”
Section: Discussionmentioning
confidence: 53%
“…KB has united a variety of interactions, such as those between genes and proteins, elements and reactions, medications and illnesses, and organisms and cells (Kanehisa et al 2019 ). Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ).…”
Section: Discussionmentioning
confidence: 53%
“…Changes in the morphology of hyphae and microconidia after treatment with medium are thought to occur due to the bioactive compounds contained therein. The first research reported that the P. azotoformans UICC B-91 medium solution contains alkaloids [9]. Alterations in the structure of hyphae and microconidia occur after administration of alkaloid compounds that are able to disrupt cell membranes, causing cell lysis and the release cell components [31].…”
Section: Discussionmentioning
confidence: 99%
“…After 12 days of incubation, the results showed that T. rubrum did not grow after being inoculated into P. aeruginosa culture. In a before study reported that testing of P. azotoformans UICC B-91 medium solution against C. albicans ATCC 10231 was carried out using the disc diffusion method [9]. Medium with a concentration of 10 mg/mL and 50 mg/mL had an average zone of inhibition value of 11.50 ± 0.71 mm and 13.25 ± 0.35 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The selected bioactive compound (Table 1) based on previous fractionation and identification of the extract by thin-layer chromatography (TLC) and liquid chromatography-mass spectrophotometry (LCMS-MS). They detected several compounds of P. azotoformans UICC B-91, including futoamide (C 18 H 23 NO 3 ), gentialutine (C 9 H 11 NO), gentiabetine (C 9 H 11 NO 2 ),1-[(2E,4E)-2,4-decadienoyl] pyrrolidine (C 14 H 23 NO), lycopodine (C 16 H 25 NO) and dihydrolycopodine (C 16 H 27 NO) (Pratiwi et al, 2022).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Based on phylogenetic analysis of nucleotide sequence generated from 16S rRNA region, two endophytic bacteria isolates isolated from N. altissima determined as P. aeruginosa and one isolate belongs to P. azotoformans (Pratiwi et al, 2016). (Pratiwi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%